Advanced penetration testing for highly-secured environments : employee the most advanced pentesting techniques and tools to build highly-secured systems and environments /: employee the most advanced pentesting techniques and tools to build highly-secured systems and environments. (2016) - Allen, Lee; Cardwell, Kevin
No abstract available